2014
DOI: 10.1371/journal.pone.0087267
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Arginine Methyltransferase 6 from Trypanosoma brucei

Abstract: Arginine methylation plays vital roles in the cellular functions of the protozoan Trypanosoma brucei. The T. brucei arginine methyltransferase 6 (TbPRMT6) is a type I arginine methyltransferase homologous to human PRMT6. In this study, we report the crystal structures of apo-TbPRMT6 and its complex with the reaction product S-adenosyl-homocysteine (SAH). The structure of apo-TbPRMT6 displays several features that are different from those of type I PRMTs that were structurally characterized previously, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
6
23
0
1
Order By: Relevance
“…Similar to other solved type I PRMT structures, including PRMT1 [46, 47], PRMT3 [48, 49], CARM1/PRMT4 [50, 51], mouse PRMT6 [52] and Trypanosoma brucei PRMT6 ( Tb PRMT6) [53], the catalytic domain of human PRMT6 consists of two domains, i.e. , the N-terminal Rossmann fold, and the C-terminal β-barrel domain with a dimerization arm embedded within it (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Similar to other solved type I PRMT structures, including PRMT1 [46, 47], PRMT3 [48, 49], CARM1/PRMT4 [50, 51], mouse PRMT6 [52] and Trypanosoma brucei PRMT6 ( Tb PRMT6) [53], the catalytic domain of human PRMT6 consists of two domains, i.e. , the N-terminal Rossmann fold, and the C-terminal β-barrel domain with a dimerization arm embedded within it (Fig.…”
Section: Resultssupporting
confidence: 61%
“…In regard to possible PRMT multimerization, we show here that TbPRMT1 forms a tetramer in vitro and sediments at a size corresponding to a tetramer in wild type cell lysate separated on a glycerol gradient. Based primarily on crystallographic studies, types I and III PRMTs are considered to function predominantly as homodimers with the exception of yeast PRMT1 (HMT1) (23,27,36,37,56,57). However, two recent structural studies of human PRMT8 revealed a tetrameric enzyme bound to a single molecule of AdoMet per canonical dimer (31) or a possible octameric helical assembly (38).…”
Section: Promentioning
confidence: 99%
“…Ce PRMT5 forms a homodimer in which the dimerization arm of one monomer interacts with residues contained in the TIM barrel of the other monomer, forming a ring [26]. This head-to-tail ring-shaped homodimer is conserved in all of the solved Type I PRMT structures [2733]. In contrast, the human and Xenopus PRMT5s form a heterooctomeric complex composed of four PRMT5 proteins and four MEP50 proteins (Fig.…”
Section: Introductionmentioning
confidence: 99%